Structure of Interaction between the Territorial Agencies and Institutions and Extraterritorial Mobile Complexes in the Course of Prevention and Response to Emergency Situations of Sanitary-Epidemiological Character (by the Example of Universiade, 2013) - G. G. Onishchenko; M. A. Patyashina; I. G. Karnaukhov; V. B. Ziatdinov (Проблемы особо опасных инфекций, 2015)
The paper provides scientific substantiation for the deployment of auxiliary forces and facilities for the provision of sanitary-epidemiological welfare of the population under mass events with international participation. Identified are the tasks and key areas of the specialized anti-epidemic teams (SAET) of the Rospotrebnadzor activities during the preparation and carrying out of the XXVII World Summer Universiade in Kazan. Reviewed are the aspects of inter-agency cooperation between the network structures and mobile units of sanitary-epidemiological and medical-preventive bias during Universiade, 2013.